25 Findings of the Study of Road Trauma Evidence and Data (SORTED). (20th November 2022) - Isles, Siobhan; Merwe, Zeeman Van der; Lewis, Chris; Grahan, Paul; Civil, Ian; Swain, Andy; Stevenson, Adam; Dicker, Bridget; Swift, Kane
Abstract : Background: Road traffic injuries are associated with high societal costs in health and financial terms. Deaths are reported to a high degree of accuracy, but there are significant gaps in injury data. SORTED was commenced to determine whether these gaps could be addressed. Method: Eight health and transport agencies brought together data from seven databases from 2017/18 and 2018/19 and agreed definintions. Using the National Health Index (NHI) to match individual patients an overall picture of the numbers of road injuries was determined. Results: 43, 500 people were injured on New Zealand roads each year, with severity ranging from minor (N=30, 700, 70%), moderate (N=11, 400, 26%), serious (N= 1, 000, 2.3%) and fatal (N=381, 1%). The rates of moderate and serious in SORTED were over four times higher than traditional metrics reported. Police investigations of hospitilised injuries varied by modes of transport, with low rates recorded for bicycle (19%) and motorbike (38%). People who live in low socioeconomic areas, males, car occupants, motorcyclists and cyclists had higher injury rates. The burden of serious injury on Māori was 70% higher than non-Māori. 18% of those injured had a subsequent road related injury within the next 24-months. The direct costs for all people injured on roads in 2018/19 was 1.03 billion. The serious injury cohort comprised 2% of caseload but 52% of cost. Conclusions: The study proved the feasibility of the methodology and addressed important gaps in the understanding of road trauma. It demonstrated the potential for collaboration between disparate agencies to provide additional value for all.